Evaluating Individual Characteristics’ Work Engagement of Primary School Teachers Moderated by Organisational Factors in Acholi-Sub Region, Uganda - Olanya, Gilbert; Okongo, Wilberforce (East African Journal of Education Studies, 2025)
This paper presents the influence of individual characteristics on primary school teachers’ work engagement as moderated by organizational management factors in northern Uganda. The main objective was to examine the influence of individual characteristics on the work engagement of primary school teachers in the Acholi sub-region. By applying a cross-section survey design, the study employed both qualitative and quantitative research methods. The primary data were collected using a self-administered questionnaire form with a total sample of 326 participants from the selected schools. Data collected were analyzed using descriptive statistics. The findings revealed that the rate of teacher absorption as well as their self-efficacy was higher than their professional dedication and commitment to their academic service delivery. In conclusion, individual teacher characteristics were vital for the work engagement outputs of the school teachers to promote school work engagement in the Acholi northern Uganda’s sub-region. The study recommended that the headteachers, education officers, boards, committees, and the government should approve individual factors that promote the work engagement ethics of the primary school teachers for better performance.